Effects of Bullying on Pupil’s Self Esteem in Al-Basra Primary Schools (Medico Legal Update, 2021)
Background: Bullying is a worldwide issue that can be seen in any school; it is not limited to one type ofpublic, private, primary or secondary, urban or rural institution and, as a result, brings anxiety, decreasedschool absenteeism, academic school performance, and can even contribute to the suicide of bullying victims.Aim: To examine Effects of Bullying on Pupil’s Self Esteem in Al-Basra primary schools.Methodology: Non-probability (purpose) sample of 300 primary school students Systemic randomlyselected from a total of 400 schools in Basra Governorate in Al Basra City Center was diagnosed as victimsby administrators and teachers from a sample of 40 primary schoolsResults: The findings indicate that the level of bullying towards primary school students was high and thelevel of self-esteem was low. There is a negative statistically association between bullying and self-esteem,which means that self-esteem has declined as bullying has increased.Conclusion: There is a negative association between self-esteem and bullying. A highly statisticallysignificant relationship exists between the self-esteem of the students and their gender and grade. A nonsignificant relationship exists between the self-esteem of the learners and their age.